The implication of Dichomitus squalens laccase isoenzymes in dye decolorization by immobilized fungal cultures - Susla, Martin; Novotný, Cenek; Svobodová, Katerina (Bioresource technology, 2007)
The study focuses on the production of ligninolytic enzymes and dye degradation capacity of Dichomitus squalens immobilized on polyurethane foam (PUF) or pine wood (PW) in a fixed bed reactor at a laboratory scale (working volume of 0.6l). Immobilization of fungal cultures on pine wood improved eminently laccase production in comparison to the liquid cultures. Immobilized D. squalens was able to decolorize an anthraquinone dye Remazol Brilliant Blue R and an azo dye Reactive Orange 16, however, only a limited decolorization of Copper(II)phthalocyanine dye was observed in both types of reactor cultures. The involvement of a laccase activity in dye decolorization was suggested. Further, two different chromatographical forms of laccases, Lc1 and Lc2, were isolated from PW cultures of D. squalens using a fast, two step FPLC method. Enzymes revealed identical molecular masses of 68 kDa (estimated by SDS-PAGE) and similar pI's, however, they differed in their catalytic properties such as pH dependence of the activity and ABTS oxidation rates. In this study, we demonstrated different dye decolorization capacities of Lc1 and Lc2 as well.
Keywords: Coloring Agents; izoenzymy; Laccase; kultivační techniky; Polyurethanes; Pinus; Polyporaceae; indoly; lakasa; dřevo; polyurethany; Organometallic Compounds; Wood; borovice; Anthraquinones; barvicí látky; Indoles; Isoenzymes; Culture Techniques; anthrachinony; organokovové sloučeniny